Study of photocatalytic activity of Bi2WO6 tire‐like microstructure. Issue 10 (21st June 2021) - Shokraiyan, Javad; Jahed, Vahdat; Rabbani, Mahboubeh
Abstract: Bi2 WO6 tire‐like microstructure assembled from 2D plates was synthesized by a simple one‐step hydrothermal method using oleic acid as a green capping agent. Bi2 WO6 photocatalyst was capable of activating hydrogen peroxide to obtain high degradation efficiency in the photocatalytic process. The catalytic performance was found to be strongly affected by the parameter of H2 O2 dosage. Furthermore, the existence of hydroxyl radical in the reaction medium was verified using radical scavengers. The effective photocatalytic activity can be attributed to the visible‐light‐driven advanced oxidation processes. Abstract : The novel tire‐like Bi2WO6 microstructure were synthesized by a simple hydrothermal method using oleic acid as a green and inexpensive capping agent. Furthermore, we employ a green advanced oxidation method of combining Bi2WO6 photocatalyst with H2O2 under visible light for organic contaminant degradation.